Assessment of Indoor and Water Radon Concentrations in Esenyurt and Beylikdüzü Districts of Istanbul, Marmara Region, Turkey - Özdemir, Firdevs Banu; Büyükuslu, Halim; Öge, Tuba Özdemir; Öge, Tuba Özdemir (My University, 2024)
The radon activity concentration measurements for indoor and tap water were studied in Esenyurt and Beylikdüzü districts of Istanbul Province, Turkey. The mean radon concentration value received from thirty-six passive radon detectors was obtained as 63.56 Bq/m3. The mean annual effective dose for indoor radon measurements is 1.60 mSv/y in this measurement period. The radon activity results of calculated tap water samples were under 0.8 Bq/L. The annual effective doses resulting from ingestion and inhalation were calculated to evaluate the health risk across various age groups. All radon measurement results, and the associated calculated data for ingestion and inhalation remained below the threshold values established by international organizations
Keywords: Su Kaynakları; Mühendislik; Jeoloji; Radon; Dose; Indoor; Tap Water; LSC